Thiessen and Kaden on Paul and the Gentiles - Hayes, Christine Elizabeth 1960-; Thiessen, Matthew 1977-; Kaden, David A. 1977- (2017)
While Matthew Thiessen's Paul and the Gentile Problem and David Kaden's Matthew, Paul, and the Anthropology of Law employ different methods to explore Paul's inclusion of Gentiles, their results are complementary and can be drawn together in a way that advances scholarly understanding of this critical issue.
Keywords: Apostle Paul; Gentiles; Judaism; Judaizing; Exclusivism; Inclusivism; Law; legal fiction